PEMAKNAAN GENERASI Z DI BANDAR LAMPUNG TERHADAP MUSIK SEBAGAI MEDIA SELF HEALING: ANALISIS RESEPSI LIRIK LAGU “REHAT” KARYA KUNTO AJI - Wulandari, Nadila; Andi Windah; Abdul Firman Ashaf (Jurnal Komunikasi Kesehatan, 2024)
Music is not only entertainment, but also has an important role in human life, one of which is as a medium of communication. In some studies, music is also used as therapy and counseling in overcoming mental health problems. Research also shows that Generation Z is more prone to mental health problems. In dealing with mental health problems, each individual has their own way to manage and relieve stress, one of which is listening to music as a form of self-healing. One of the music that is claimed to be self-healing is the song “Rehat” by Kunto Aji. Music as part of popular culture products can be a powerful medium to convey messages about mental health and self-healing. This study aims to determine the reception of generation Z in Bandar Lampung towards music as a medium of self-healing in the lyrics of the song Rehat. This research uses a descriptive qualitative approach with the theory of reception analysis by Stuart Hall. Data were collected through in-depth interviews and documentation to 6 informants who have different background experiences and self-defense mechanisms. Data were collected by conducting in-depth interviews with informants who are generation Z, listen to Rehat songs, and have experienced or are experiencing stress. The results of this study show that generation Z is in two positions, namely hegemony position and negotiation position in the process of interpreting self healing in the lyrics of the song “Rehat” by Kunto Aji.